Real world prognostic utility of platelet lymphocyte ratio and nutritional status in first-line immunotherapy response in stage IV non-small cell lung cancer - Madeline MacDonald; Darin Poei; Alexis Leyba; Raymond Diep; Krithika Chennapan; Christopher Leon; Bing Xia; Jorge J. Nieva; Robert Hsu (Cancer Treatment and Research Communications, 2023)
Background: Elevated platelet lymphocyte ratio (PLR) and low body mass index (BMI) are associated with inferior survival in non-small cell lung cancer (NSCLC) patients receiving immunotherapy (IO). We evaluated real-world prognostic utility of PLR, BMI, and albumin level in stage IV NSCLC patients receiving first line (1L) IO. Methods: We identified 75 stage IV patients who received 1L IO therapy at USC Norris Comprehensive Cancer Center and Los Angeles General Medical Center from 2015 to 2022. The primary outcome was overall survival (OS) from time of IO with attention to pre-treatment BMI < 22, albumin < 3.5 g/dL, and PLR > 180. Results: Median age was 66.5 years with 49 (65.3%) males. 25 (33.3%) had BMI < 22. 45/75 (60%) had PLR > 180. Patients with BMI < 22 had inferior OS (13.1 months (m) vs. 37.4 m in BMI > 28, p-value = 0.042) along with patients with albumin<3.5 g/dL (OS: 2.8 m vs. 14.6 m, p-value = 0.0027), and patients with PLR>180 (OS: 8.7 m vs. 23.0 m, p = 0.028). Composite BMI < 22, PLR > 180 had the worst OS, p-value = 0.0331. Multivariate analysis controlling for age, smoking, gender, PD-L1 tumor proportion score (TPS), and histology (adenocarcinoma, squamous, adenosquamous, and large cell) showed that BMI (HR: 0.8726, 95% CI: 0.7892–0.954) and PLR > 180 (HR: 2.48, 95% CI: 1.076–6.055) were significant in OS mortality risk. Conclusion: Patients with a composite of BMI < 22, albumin < 3.5 g/dL, and PLR > 180 had significantly worse OS. This highlights the importance of screening for poor nutritional status and high PLR to better inform stage IV NSCLC patients receiving IO therapy of their prognosis and supportive care. MicroAbstract: We evaluated real-world prognostic utility of platelet lymphocyte ratio (PLR), body mass index (BMI), and albumin level in 75 Stage IV NSCLC patients receiving first line IO. Patients with a composite of BMI < 22, albumin < 3.5 g/dL, and PLR > 180 had significantly worse OS. This highlights the importance of screening for poor nutritional status and high PLR to better inform stage IV NSCLC patients of their prognosis and to emphasize supportive care needs.